Implant Stability Outcomes After Immediate and Delayed Revascularized Free Fibula Flaps: A Preliminary Comparative Study - SAÇAK, BÜLENT; DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR (QUINTESSENCE PUBLISHING CO INC, 2018)
Purpose: This pilot study investigated the retrospective outcomes of implants placed immediately or with a delayed protocol in revascularized free fibula flaps (FFF). Materials and Methods: Patients undergoing FFF between 2014 and 2017 were included in the study. Implants were inserted either immediately or 23.63 +/- 10.61 months after reconstructive surgery. Resonance frequency analyses were recorded at the time of implant placement (first control) and 4 months postoperatively while uncovering and screwing the gingiva formers (second control). The statistical significance level was set at P < .05. Results: Eight patients (four men, four women, mean age: 46.75 +/- 12.96 years) were included in the study. Twenty-six implants were placed in FFF (14 immediate, 12 delayed), and 28 were placed in the alveolus. All implant stability quotient (ISQ) scores were in high stability ranges. Statistically significant differences were observed between delayed (79.25 +/- 4.77) and immediate implant placement (73.14 +/- 7.42) at first controls, but not at second controls (79.17 +/- 3.59 and 76.00 +/- 6.18). The ISQ values of immediate implant placement significantly increased from first to second controls (P = .018). Bicortically placed implants showed significantly higher scores than unicortical implants (P < .05). ISQ values of FFF and alveolar bone groups were similar (P > .05). Conclusion: High stability scores similar to alveolar bone could be achieved by both immediate and delayed implant placement. Bicortical implantation results in better implant stability.
Keywords: dental implant; implantation times; resonance frequency analyses; revascularized free fibula flap; RESONANCE FREQUENCY-ANALYSIS; QUALITY-OF-LIFE; DENTAL IMPLANTS; MANDIBULAR RECONSTRUCTION; TITANIUM IMPLANTS; IN-VITRO; REHABILITATION; INTERFACE; MANDIBLES; DEFECTS